STRATEGI KOMUNIKASI PEMASARAN RRI MALANG DALAM UPAYA PENCAPAIAN PNBP DAN MENINGKATKAN JUMLAH PENGIKLAN - Yulius; Prasetya Widodo, Herru (Unitri Press, 2019)
RRI Malang as a Public Broadcasting Institution continues to survive amid intense competitions, with the demands to meet the target of achieving Non-Tax State Revenues (PNBP), which rely on the main source of revenue such as advertising but are bound by the Government Regulation No. 5 of 2015. The research aimed to find out how the marketing communication strategy of RRI Malang and the obstacles in implementing the strategy in an effort to achieve Non-Tax State Revenue (PNBP) and increase the number of Advertisers. This research used a descriptive qualitative research method with the data collection obtained from interviews and documents then collected and described. The result showed that the strategies applied by RRI Malang were market opportunity analysis and a competitive analysis which is summarized to an integrated marketing communication (IMC) which included: advertising in the form of price advertising, brand advertising and institutional advertising. A direct marketing through media channels such as catalogs, and telemarketing. The sales promotions were through broadcast programs, general and functional advertisements. The personal selling was through personal face-to-face communication. Furthermore, public relations (branding relations) activities were such as making press releases for each activity and becoming a media partner. The Barriers to the implementation of strategies were the limited funding sources and scope to collaborate with sponsors, advertisement selection was difficult to display discounts, because they were bound by the regulation No.5 of 2015 and lack of Human Resources (HR) and discrepancies between tasks and functions in the field of work.